1975
DOI: 10.1139/m75-005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo interactions between Erwinia amylovora and related saprophytic bacteria

Abstract: Under carefully controlled laboratory conditions, a highly virulent strain of Erwinia amylovora coinhabited susceptible host tissues with a yellow saprophytic bacterium, which was invariably isolated from fire blight infected trees, with or without producing symptoms of the disease depending on the status of a number of environmental factors, both climatic and physiological. In particular, variation of temperature and sucrose concentration determined, independently, the equilibrium of a readily reversible alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…The presence of E. herbicola, an apparent saprophyte, and E. carotovora a known phytopathogen bears a similarity to the relationship between E. herbicola and E. amylovora in fireblight cankers of fruit trees (Rosaceae) described by RIGGLE et al (1972) and ERSKINE et al (1975). In the case of fireblight the high numbers of E. amylovora in young cankers are succeeded by increasing populations of E. herbicola as cankers begin to age.…”
Section: Discussionsupporting
confidence: 53%
“…The presence of E. herbicola, an apparent saprophyte, and E. carotovora a known phytopathogen bears a similarity to the relationship between E. herbicola and E. amylovora in fireblight cankers of fruit trees (Rosaceae) described by RIGGLE et al (1972) and ERSKINE et al (1975). In the case of fireblight the high numbers of E. amylovora in young cankers are succeeded by increasing populations of E. herbicola as cankers begin to age.…”
Section: Discussionsupporting
confidence: 53%
“…Although several authors have suggested that production of antibiotics by E. herbicola could be involved in biological control of fire blight (17,27,28,61), others have disagreed, since no inhibitory compound could be detected for some strains that are effective in the orchard. This was the case for Eh252 (2), until R. S. Wodzinski (63) showed that Eh252 inhibited E. amylovora in minimal medium in the absence of histidine.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained suggest that antibiotic production is a determinant of the biological control of E. amylovora by Eh252, but that another mechanism(s) is involved. Nonpathogenic yellow-pigmented bacteria, not always formally identified as E. herbicola, are often isolated from diseased plant tissues in association with the closely related bacterium Erwinia amylovora (17,26,38,40,64). E. amylovora causes fire blight, a typical necrotic disease that affects all plant species of the Pomoideae but is especially destructive to apple and pear trees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated a potential for biological control of fire blight (Shaw 1929;Parker 1936;Farabee and Lockwood 1958;Goodman 1965Goodman , 1967Erskine 1973;McIntyre et al 1973;Wrather et al 1973;Erskine and Lopatecki 1975). Shaw (1929) and Parker (1936) used non-pathogenic yellow bacteria that later were recognized as Erw.…”
Section: Introductionmentioning
confidence: 99%